(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
The bolted joints in the leg and the bracing members of the lattice transmission towers are always subjected to predominant axial forces, which will cause joint slip that greatly af- fects the global behaviour of the whole structure. The paper shows the results of the numerical modelling of the response of the steel lattice communication tower, with height h = 40.5 m located in Rzeszów. A comparison was made of five tower models, differing in the characteristics of the joint force-elongation relationship, including stiffness of the components and also joint slippage, coming from Category A joints. The paper presents the difference in displacements and rotations of chosen tower panels, internal forces in leg members, as well as in the fundamental flexural frequen- cy obtained without considering the force-displacement characteristic and with four different ways of modelling of joints behaviour.